Porous Porphyrin‐Based Organosilica Nanoparticles for NIR Two‐Photon Photodynamic Therapy and Gene Delivery in Zebrafish. (30th March 2018) - Mauriello Jimenez, Chiara; Aggad, Dina; Croissant, Jonas G.; Tresfield, Karen; Laurencin, Danielle; Berthomieu, Dorothée; Cubedo, Nicolas; Rossel, Mireille; Alsaiari, Shahad; Anjum, Dalaver H.; Sougrat, Rachid; Roldan‐Gutierrez, Manuel A.; et al.
Abstract: Periodic mesoporous organosilica nanoparticles emerge as promising vectors for nanomedicine applications. Their properties are very different from those of well‐known mesoporous silica nanoparticles as there is no silica source for their synthesis. So far, they have only been synthesized from small bis‐silylated organic precursors. However, no studies employing large stimuli‐responsive precursors have been reported on such hybrid systems yet. Here, the synthesis of porphyrin‐based organosilica nanoparticles from a large octasilylated metalated porphyrin precursor is described for applications in near‐infrared two‐photon‐triggered spatiotemporal theranostics. The nanoparticles display unique interconnected large cavities of 10–80 nm. The framework of the nanoparticles is constituted with J‐aggregates of porphyrins, which endows them with two‐photon sensitivity. The nanoparticle efficiency for intracellular tracking is first demonstrated by the in vitro near‐infrared imaging of breast cancer cells. After functionalization of the nanoparticles with aminopropyltriethoxysilane, two‐photon‐excited photodynamic therapy in zebrafish is successfully achieved. Two‐photon photochemical internalization in cancer cells of the nanoparticles loaded with siRNA is also performed for the first time. Furthermore, siRNA targeting green fluorescent protein complexed with the nanoparticles is delivered in vivo in zebrafish embryos, which demonstrates the versatility of the nanovectors for biomedical applications. Abstract : The synthesis of porous porphyrin‐based organosilica nanoparticles is described. The porphyrins form J aggregates that allow two‐photon excitation of the nanoparticles. Two‐photon photodynamic therapy of tumors implanted in zebrafish is very efficient. Two‐photon photochemical internalization in cancer cells is demonstrated and siRNA targeting green fluorescent protein is also successfully delivered in the zebrafish model.